Expression of microRNA-155 in circulating T cells is an indicator of immune activation levels in HIV-1 infected patients. Issue 3 (2nd September 2021) - Zhang, Zhenghao; Wu, Yong; Chen, Jiangnan; Hu, Fangqing; Chen, Xuefang; Xu, Wenfang
Abstract : Objectives: MicroRNA-155 (miR-155) regulates activation of T cells. However, its relationship with T-cell immune activation level in human immunodeficiency virus (HIV) patients remains unclear. Methods: We recruited 103 HIV-1 infected patients with combination antiretroviral therapy (cART) and 79 cART naïve patients. The miR-155 levels in circulatory T cells were detected by quantitative reverse transcription–PCR. T cell immune activation was detected by the expression of CD38 via flow cytometry. Results: The levels of miR-155 in the total peripheral blood mononuclear cells, CD4+, and CD8+ T cells from HIV-1 patients were increased ( p < 0.01). cART naïve patients exhibited much higher miR-155 levels in CD4 + and CD8+ T cells than patients with cART( p < 0.01). The percentage of CD4 + CD38+ T and CD8 + CD38+ T cells was also increased in cART naïve patients ( p < 0.01). MiR-155 level was positively related to immune activation of T cells. Conclusion: Our findings suggest that miR-155 levels in circulating T cells of HIV-1 patients are increased and associated with T cell activation.